Habitat productivity predicts the global distribution of social spiders - Majer, Marija; Svenning, Jens-Christian; Bilde, Trine (Frontiers in Ecology and Evolution, 2015)
Permanently-social spiders share a common suite of traits, including cooperative foraging and brood care, elimination of pre-mating dispersal, and the transition to an inbreeding mating system. Social spiders are confined to tropic and subtropical habitats, suggesting environmental constraints on the evolution of group living in spiders. Because social spider groups are sedentary and dependent on arrival of insect prey in their capture webs, group living and the associated higher local density is expected to rely on a relatively resource rich environment. We used spatial statistical modelling to explore environmental factors underlying the macro-ecological patterns in the distribution and diversity patterns of social spiders. We found strong support for habitat productivity as a predictor of the distribution of social species, particularly in the Old World. We show that social species are restricted to more productive habitats relative to a set of closely related subsocial sister species with a solitary lifestyle. Within their distribution range, social species richness was higher where precipitation seasonality is lower. These macro-ecological patterns corroborate the underlying biological hypotheses that evolution of group living is facilitated in environments that provide more abundant insect prey and a more continuous supply of food resources.